Analysis of Financial Difficulties in Financial Management with Altman Z-Score, Zmijewski, and Springate Models in Small Textile and Apparel Companies Listed on the Indonesia Stock Exchange - Marjohan, Masno (JURNAL AKUNTANSI DAN MANAJEMEN, 2024)
Financial difficulties are the first step experienced by a company in the bankruptcy process. If the company fails, many parties are harmed. Therefore, it is necessary to conduct an analysis of financial problems or difficulties that can provide early warning for the company. The purpose of this study is to find out and analyze financial difficulties in financial management with the ALTMAN Z-SCORE, ZMIJEWSKI, and SPRINGATE models in small textile and apparel companies listed on the Indonesia Stock Exchange (IDX) using the calculation of the Altman Z-Score, Zmijewski, and Springate models. The research method used is quantitative descriptive research. The research population is all textile and garment subsector companies listed on the IDX as many as 25 companies. The samples were selected using a purposive sampling technique and were obtained by 6 companies over a six-year period. The data analysis models used are the Altman Original Z-Score, Zmijewski, and Springate models. This research was conducted by taking secondary data from the Indonesia Stock Exchange website. The results of the study show that there are companies in the textile and garment subsector that are experiencing financial difficulties and financial management with the model used. Zmijewski's model is the most accurate in predicting financial difficulties with the highest accuracy of fifty percent.